Analisis Kebutuhan pada Integrasi ChatGPT dan Python dalam Asesmen Diagnostik Pembelajaran Matematika di Sekolah Dasar - Aziz, Khatmirul; Nugroho, Heru Siddik; Wahyuningsih, Putri Indah; Tuningsih, Suci; Hidayah, Nisrina Ajrina Nur (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The development of Artificial Intelligence (AI) has created new opportunities for innovation in educational assessment, particularly in mathematics learning at the elementary school level, which requires accurate identification of students’ prior knowledge. This study aims to analyze the needs and urgency of integrating ChatGPT and Python in the development of diagnostic assessments for elementary school mathematics learning. The study employed a quantitative approach with a cross-sectional survey design. The research subjects were elementary school teachers in Kranggan District, Temanggung Regency, selected through incidental sampling. The research instrument was a needs analysis questionnaire that had been tested for validity and reliability. Data were analyzed using descriptive quantitative techniques. The results indicate that the average response percentage reached 83%, which falls into the “strongly agree” category, demonstrating a high level of teachers’ need for diagnostic assessments based on the integration of ChatGPT and Python. These findings confirm that the utilization of artificial intelligence and programming technologies has the potential to enhance the effectiveness, efficiency, and accuracy of diagnostic assessments in elementary school mathematics learning. This study provides an initial contribution to the development of technology-based diagnostic assessments as an innovative solution aligned with the demands of the Merdeka Curriculum and 21st-century learning.